ICD coding training worldwide - Varela, Lucia Otero; Eastwood, Catherine; Mathur, Pallavi; Quan, Hude (International Journal of Population Data Science, 2018)
Introduction The International Classification of Diseases (ICD) is globally used for coding morbidity statistics, however, its use, as well as the training provided to individuals assigning codes, varies greatly across countries. Objectives and Approach The goal is to understand the quality of coder training worldwide. After an in-depth grey and academic literature review, an online survey was created to poll the 194 World Health Organization (WHO) member countries. Questions focused on hospital data collection systems and the training provided to the coding professionals. The survey was distributed to potential participants that meet the specific criteria, as well as to organizations specialized in the topic, such as WHO-CC (WHO Collaborating Centers) and IFHIMA (International Federation of Health Information Management Association), to be forwarded to their representatives. Answers will be analyzed using descriptive statistics. Results This ongoing project aims to capture responses from as many countries as possible, and thus far, data from 45 respondents from 20 different countries has been collected. Initial results reveal worldwide use of ICD, with variations in the maximum allowable coding fields for diagnoses and interventions. Coding specialists are the main personnel assigning codes, followed by physicians, and although minimum training is not mandatory in all countries (Sweden, Italy, Germany and Thailand), in those where it is, college/university degree is the most common requirement. Coding certificates most frequently entail passing a certification exam. Continuing education for coders is offered in all countries except one (Nigeria). Once more information is available, countries will be ranked and those depicting a better performance will be highlighted. Conclusion/Implications These survey data will establish the current state of ICD use and coding training internationally, which will ultimately be valuable to the WHO for the promotion of ICD and the rollout of ICD-11, for better international comparisons of health data, and for further research on how to improve ICD coding.